2011
DOI: 10.1371/journal.pone.0028040
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Biochemical Fractionation, Not Convergent Temperature, Explains Cellulose Oxygen Isotope Enrichment across Latitudes

Abstract: Recent findings based on the oxygen isotope ratios of tree trunk cellulose indicate that the temperature of biomass production in biomes ranging from boreal to subtropical forests converge to an average leaf temperature of 21.4°C. The above conclusion has been drawn under the assumption that biochemically related isotopic fractionations during cellulose synthesis are not affected by temperature. Here we test the above assumption by heterotrophically generating cellulose at different temperatures and measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
113
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 24 publications
13
113
3
Order By: Relevance
“…In accordance with DeNiro and Epstein (1981), Sternberg (1989) and Yakir and DeNiro (1990), the biochemical fractionation ε 0 is assumed here to be lower than 30 ‰. However, a recent study has demonstrated that this parameter, nearly constant between 20 to 30 • C, increases at lower temperatures to values of 31 ‰ (Sternberg and Ellsworth, 2011). During the growing season, maximum temperatures can reach 20 • C in western Argentina and 30 • C in northeastern Canada, which suggests that the high mean δ 18 O TR levels in N. pumilio may be due to biochemical fractionation higher than 30 ‰ due to temperature generally lower than 20 • C. However, when the prior range of ε 0 is extended to 31 ‰ in the optimization process, the mean δ 18 O TR levels of N. pumilio are still too low in comparison with the observations.…”
Section: Relative Performance In Modelling δ 18 O Tr Valuesmentioning
confidence: 90%
See 1 more Smart Citation
“…In accordance with DeNiro and Epstein (1981), Sternberg (1989) and Yakir and DeNiro (1990), the biochemical fractionation ε 0 is assumed here to be lower than 30 ‰. However, a recent study has demonstrated that this parameter, nearly constant between 20 to 30 • C, increases at lower temperatures to values of 31 ‰ (Sternberg and Ellsworth, 2011). During the growing season, maximum temperatures can reach 20 • C in western Argentina and 30 • C in northeastern Canada, which suggests that the high mean δ 18 O TR levels in N. pumilio may be due to biochemical fractionation higher than 30 ‰ due to temperature generally lower than 20 • C. However, when the prior range of ε 0 is extended to 31 ‰ in the optimization process, the mean δ 18 O TR levels of N. pumilio are still too low in comparison with the observations.…”
Section: Relative Performance In Modelling δ 18 O Tr Valuesmentioning
confidence: 90%
“…Ideally, daily δ 18 O P longterm records from meteorological stations in the study region should be used as an input of MAIDENiso. Simulations from high-resolution regional circulation models, such as REMOiso, which has a 0.5 • × 0.5 • (∼ 55 km) horizontal resolution (Insel et al, 2013;Sturm et al, 2005Sturm et al, , 2007, may produce reliable local δ 18 O P values. Such a dataset has proven to be quite helpful with MAIDENiso in the Fontainebleau forest (France) (Danis et al, 2012).…”
Section: Relative Performance In Modelling δ 18 O Tr Valuesmentioning
confidence: 99%
“…2) Model parameters The equilibrium (ε*) and kinetic fractionation factors (ε k ) are regarded as being relatively constant, and have been reported to be approximately 9‰ and 29‰, respectively (Allison et al, 1985). The proportion of isotopic exchange between xylem water and carbohydrate oxygen (f o ) does not vary at different temperatures (Sternberg and Ellsworth, 2011), and we adopted a previously reported value of 0.42 as the f o value for our calculations (Roden et al, 2000;Sternberg and Ellsworth, 2011). Although the net biological isotopic fractionation factor between xylem water and exchanged oxygen (ε o ) is temperature-sensitive, ε o changes little within a temperature range from 20 to 30°C (Sternberg and Ellsworth, 2011).…”
Section: Forward Modelingmentioning
confidence: 99%
“…The proportion of isotopic exchange between xylem water and carbohydrate oxygen (f o ) does not vary at different temperatures (Sternberg and Ellsworth, 2011), and we adopted a previously reported value of 0.42 as the f o value for our calculations (Roden et al, 2000;Sternberg and Ellsworth, 2011). Although the net biological isotopic fractionation factor between xylem water and exchanged oxygen (ε o ) is temperature-sensitive, ε o changes little within a temperature range from 20 to 30°C (Sternberg and Ellsworth, 2011). Monthly temperature ranged from 18 to 26°C at our sampling site, and ε o was 27‰, as has been observed in previous studies (Sternberg et al, 1984;Sternberg and DeNiro, 1983;Yakir and DeNiro, 1990).…”
mentioning
confidence: 99%
“…The application of both equations in the investigation period is primarily based on the assumption that biochemical oxygen isotope fractionation during cellulose synthesis is almost constant under different temperatures. However, Sternberg and Ellsworth (2011) proposed a temperature effect on cellulose oxygen isotope enrichment relative to source water, especially at temperatures below 20 • C. Accordingly, isotopic enrichment would increase with decreased temperature and the mean of increased enrichment between 4 and 15 • C is about 2 ‰ (Sternberg and Ellsworth, 2011). This value is, however, derived by summarizing various field studies under different analytical conditions and has not been further confirmed by the latest modern calibration data set from sites in southern Patagonia , which shows no apparent effect of host water temperature on the fractionation between aquatic cellulose and host waters.…”
Section: Reconstructed Lake Water δ 18 O Valuesmentioning
confidence: 99%